2021
DOI: 10.3389/fcell.2021.647736
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs: Their Role in the Pathogenesis and Orchestration of Breast Cancer

Abstract: As one of the most frequently occurring malignancies in women, breast cancer (BC) is still an enormous threat to women all over the world. The high mortality rates in BC patients are associated with BC recurrence, metastatic progression to distant organs, and therapeutic resistance. Circular RNAs (circRNAs), belonging to the non-coding RNAs (ncRNAs), are connected end to end to form covalently closed single-chain circular molecules. CircRNAs are widely found in different species and a variety of human cells, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 116 publications
0
14
0
Order By: Relevance
“…CircRNAs are ubiquitous non-coding RNAs in eukaryotic cells, which are diverse, stable, and evolutionarily conserved. It is gradually recognized that circRNA is dysregulated in BC tissues and participated in the pathogenesis of BC by harboring miRNAs [ 27 ]. For instance, Yang et al successfully identified a total of 47 upregulated and 307 downregulated DE circRNAs to construct the competing endogenous RNA (ceRNA) network of BC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are ubiquitous non-coding RNAs in eukaryotic cells, which are diverse, stable, and evolutionarily conserved. It is gradually recognized that circRNA is dysregulated in BC tissues and participated in the pathogenesis of BC by harboring miRNAs [ 27 ]. For instance, Yang et al successfully identified a total of 47 upregulated and 307 downregulated DE circRNAs to construct the competing endogenous RNA (ceRNA) network of BC [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs belong to a large category of endogenous ncRNAs that are structurally connected end to end to form single-chain molecules with a covalently closed loop structure ( He et al, 2021b ). Functionally, circRNAs can regulate the level of transcriptional and post-transcriptional parental genes by acting as miRNA sponges ( Kristensen et al, 2019 ).…”
Section: Mechanisms Of Ncrna In Wound Healingmentioning
confidence: 99%
“…Multiple lncRNAs have been investigated to be involved in the initiation and progression of glioma including CRNDE, H19, XIST, GAS, Malat1, HOTAIR, and SOX2OT [ 11 ]. CircRNAs are covalently closed single-chain circular molecules, which are endogenous molecules that exhibit diversity, evolutionary conservation, relative stability, and specificity [ 12 ]. CircRNAs usually function as tumor promoters or suppressors by acting as miRNA sponges to subsequently regulate transcription and splicing of their parental genes.…”
Section: Introductionmentioning
confidence: 99%